EVOLUTION AND FORMATION OF THE ISSUE OF CHANGING DEADLINES IN THE COMMERCIAL PROCESS - Zarichanska, Zoya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to analyze the norms of procedural legislation, in particular, economic legislation, which determine the procedure for restoring, renewing, and extending procedural deadlines during the consideration of a case in an economic court. Research methods: the comparative legal method was used to compare the norms of codes that regulate the concept of time limits in commercial, civil and administrative proceedings, the logical and legal method was applied to clarify the norms of procedural legislation, and the historical method was also used to analyze the formation of the studied definitions in procedural law. Results: the formation of the concepts of renewal and extension of terms in the economic process was analyzed; the problem of the impossibility of extending the terms established by the court under certain conditions, even if there are valid reasons for missing such a term, was identified. Discussion: the issue of restoration, renewal, and extension of procedural deadlines developed in parallel in commercial, civil, and administrative proceedings and eventually acquired the same features in the versions of procedural codes from December 15, 2017.The significance of the time limits for performing specific procedural actions is important in view of the need to comply with the basic principles of judicial proceedings - adversarial and equality of parties, which is a component of the concept of "right to a fair trial" within the meaning of Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms.There is currently a need to amend Article 119 of the Commercial Procedural Code of Ukraine in order to provide the participants in the case and the court with appropriate opportunities to exercise their rights to take procedural actions within a reasonable time.